Light Management in Organic Photovoltaics Processed in Ambient Conditions Using ZnO Nanowire and Antireflection Layer with Nanocone Array. Issue 25 (7th May 2019) - Tavakoli, Mohammad Mahdi; Dastjerdi, Hadi Tavakoli; Zhao, Jiayuan; Shulenberger, Katherine E.; Carbonera, Chiara; Po, Riccardo; Cominetti, Alessandra; Bianchi, Gabriele; Klein, Nathan D.; Bawendi, Moungi G.; Gradecak, Silvija; Kong, Jing
Abstract: Low carrier mobility and lifetime in semiconductor polymers are some of the main challenges facing the field of organic photovoltaics (OPV) in the quest for efficient devices with high current density. Finding novel strategies such as device structure engineering is a key pathway toward addressing this issue. In this work, the light absorption and carrier collection of OPV devices are improved by employment of ZnO nanowire (NW) arrays with an optimum NW length (50 nm) and antireflection (AR) film with nanocone structure. The optical characterization results show that ZnO NW increases the transmittance of the electron transporting layer as well as the absorption of the polymer blend. Moreover, the as‐deposited polymer blend on the ZnO NW array shows better charge transfer as compared to the planar sample. By employing PC70BM:PV2000 as a promising air‐stable active‐layer, power conversion efficiencies of 9.8% and 10.1% are achieved for NW devices without and with an AR film, indicating 22.5% and 26.2% enhancement in PCE as compared to that of planar device. Moreover, it is shown that the AR film enhances the water‐repellent ability of the OPV device. Abstract : Light management using ZnO nanowire arrays and an antireflection layer can improve the absorption of organic semiconductors and enhance the performance of organic photovoltaics.